Uptake and acceptability of oral HIV self-testing in the context of assisted partner services in Western Kenya: A mixed-methods analysis. - Victor Mudhune; Unmesha Roy Paladhi; Mercy Owuor; Kenneth Ngure; David A Katz; George Otieno; Monisha Sharma; Sarah Masyuko; Edward Kariithi; Carey Farquhar; Rose Bosire (PLOS Global Public Health)
Integrating HIV self-testing (HIVST) into assisted partner services (APS) has potential to increase identification of people with HIV in the community, but little is known about acceptability of HIVST among partners traced via APS. We assessed characteristics of APS partners testing with HIVST, and factors influencing HIVST uptake and acceptability in a cluster-randomized control trial on APS+HIVST. Using convergent parallel mixed-methods design, we evaluated socio-demographic and behavioral characteristics of APS partners who were offered HIVST or provider-delivered testing, and purposively selected a sub-set of partners for in-depth interviews (IDIs). Descriptive and log-binomial regression analyses were performed controlling for health facility clusters, while IDIs were thematically analyzed applying the theoretical framework of acceptability. Among 3312 partners who were offered HIVST or provider-administered testing through APS, 2724 (82.2%) used HIVST. There was no association between partner demographics and HIVST uptake. HIVST use was less likely than provider-delivered testing among those identified as a casual (adjusted relative risk (aRR) = 0.93; 95% Confidence Interval (CI) 0.88-0.98) or transactional (aRR = 0.90; 95% CI 0.87-0.94) partner compared to those in a defined relationship. HIVST use was slightly lower among those offered the option of an additional kit when compared to those only offered one kit (aRR = 0.93; 95% CI 0.88-0.98). In the IDIs (N = 24), partners reported that HIVST was a viable option for individuals who do not find provider-delivered testing suitable or convenient. For the APS partners, 'intervention coherence', 'self-efficacy', and 'ethicality' presented as most significant theoretical framework of acceptability constructs. APS providers played a critical role in creating HIVST awareness and driving acceptability. Increasing HIVST awareness and providing tailored solutions will empower APS clients optimize their HIV testing decisions. Providers should consider context of the partner's sexual encounter and extend counselling support when recommending HIVST within APS.